Genetic and physical map of the von Recklinghausen neurofibromatosis (NF1) region on chromosome 17. - Yagle, M K (1990)
The von Recklinghausen neurofibromatosis 1 (NF1) locus has been previously assigned to the proximal long arm of chromosome 17, and two NF1 patients have been identified who have constitutional balanced translocations involving 17q11.2. We have constructed a cosmid library from a chromosome-mediated gene transfectant, KLT8, that contains approximately 10% of chromosome 17, including 17q11.2. Cosmids isolated from this library have been mapped across a panel of somatic cell hybrids, including the hybrids from the two patients, and have been localized to seven small regions of proximal 17q. We have 5 cosmids that map directly above the two NF1 translocations, and 11 cosmids that map directly below. Of these, 2 cosmids in each region are linked to the disease locus and 3 of these cosmids show no recombination. One distal cosmid, 2B/B35, detects the two NF1 translocations by pulsed-field gel analysis and has been used to produce a long-range restriction map that covers the translocations.